No evidence of male-biased sexual selection in a snake with conventional Darwinian sex roles. Issue 10 (7th October 2020) - Levine, Brenna A.; Schuett, Gordon W.; Clark, Rulon W.; Repp, Roger A.; Herrmann, Hans-Werner; Booth, Warren
Abstract : Decades of research on sexual selection have demonstrated that 'conventional' Darwinian sex roles are common in species with anisogamous gametes, with those species often exhibiting male-biased sexual selection. Yet, mating system characteristics such as long-term sperm storage and polyandry have the capacity to disrupt this pattern. Here, these ideas were explored by quantifying sexual selection metrics for the western diamond-backed rattlesnake ( Crotalus atrox ). A significant standardized sexual selection gradient was not found for males ( β SS = 0.588, p = 0.199) or females ( β SS = 0.151, p = 0.664), and opportunities for sexual selection ( Is ) and selection ( I ) did not differ between males ( Is = 0.069, I = 0.360) and females ( Is = 0.284, I = 0.424; both p > 0.05). Furthermore, the sexes did not differ in the maximum intensity of precopulatory sexual selection (males: s′ max = 0.155, females: s′ max = 0.080; p > 0.05). Finally, there was no evidence that male snout–vent length, a trait associated with mating advantage, is a target of sexual selection ( p > 0.05). These results suggest a lack of male-biased sexual selection in this population. Mating system characteristics that could erode male-biased sexual selection, despite the presence of conventional Darwinian sex roles, are discussed.